Dark Chaucer: An Assortment - Masciandaro, Nicola, 1969-; Joy, Eileen A., 1962-; Seaman, Myra; Project Muse; Project Muse. (Project Muse, 2020)
Although widely beloved for its playfulness and comic sensibility, Chaucer's poetry is also subtly shot through with dark moments that open into obscure and irresolvably haunting vistas, passages into which one might fall head-first and never reach the abyssal bottom, scenes and events where everything could possibly go horribly wrong or where everything that matters seems, if even momentarily, altogether and irretrievably lost. And then sometimes, things really do go wrong. Opting to dilate rather than cordon off this darkness, this volume assembles a variety of attempts to follow such moments into their folds of blackness and horror, to chart their endless sorrows and recursive gloom, and to take depth soundings in the darker recesses of the Chaucerian lakes in order to bring back palm- or bite-sized pieces (black jewels) of bitter Chaucer that could be shared with others ... an "assortment," if you will. Not that this collection finds only emptiness and non-meaning in these caves and lakes. You never know what you will discover in the dark.
and here we are as on a darkling plain / Gary J. Shipley -- Dark whiteness : Benjamin Brawley and Chaucer / Candace Barrington -- Saturn's darkness / Brantley Bryant & Alia -- A dark stain and a non-encounter / Ruth Evans -- Chaucerian afterlives : reception and eschatology / Gaelan Gilbert -- Black gold : the former (and future) age / Leigh Harrison -- Half dead : parsing Cecelia / Nicola Masciandaro -- In the event of the Franklin's tale / J. Allan Mitchell -- Black as the crow / Travis Neel and Andrew Richmond -- Unraveling Constance / Hannah Priest -- L'O de V : a palimpsest / Lisa Schamess -- Disconsolate art / Myra Seaman -- Kill me, save me, let me go : Custance, Virginia, Emelye / Karl Steel -- The Physician's tale as hagioclasm / Elaine Treharne -- The light has lifted : trickster Pandare / Bob Valasek -- Suffer the little children, or, a rumination on the faith of zombies / Lisa Weston -- The dark is light enough : the layout of The tale of Sir Thopas / Thomas White.
Issued as part of book collections on Project MUSE.
Includes bibliographical references.
Description based on print version record.
Keywords: Chaucer, Geoffrey, -- -1400.; Chaucer, Geoffrey, -- -1400 -- Criticism and interpretation; Light and darkness in literature; Electronic books; Electronic books